2022
DOI: 10.3389/fphar.2022.852042
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Vortioxetine in the Treatment of Depressive Symptoms in Patients With Epilepsy—Case Series

Abstract: Epilepsy and depression are both serious and potentially disabling conditions which often coexist—bidirectional relationship between the two disorders has been observed. Comorbidity between depression and epilepsy can be attributed to: underlying common pathophysiological mechanisms, psychiatric side effect of antiepileptic medications and psychological response to stress in people with chronic, neurological condition. Despite high prevalence of depressive symptoms in patients with epilepsy, current evidence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
0
0
1
Order By: Relevance
“…Interestingly, for our purposes, vortioxetine was found safe in the case of a suicidal attempt by overdosage (250 mg), with no changes in blood pressure, electrocardiogram, creatinine and only modest changes in g-glutamyl-transferase levels (71 U/L twenty-four hours after ingestion) [146]. A case series showed that vortioxetine (10-20 mg/day) was safe and effective in a sample of nine patients suffering from epilepsy (seven cases were structural, and two were cryptogenetic) without any apparent destabilization of epileptic thresholds [147]. A report found a favourable outcome after three months 10 mg/day vortioxetine treatment in a patient with rapid eye movement (REM) sleep behaviour disorder previously treated with paroxetine and melatonin without benefit [148].…”
Section: Descriptive Observational Studiesmentioning
confidence: 99%
“…Interestingly, for our purposes, vortioxetine was found safe in the case of a suicidal attempt by overdosage (250 mg), with no changes in blood pressure, electrocardiogram, creatinine and only modest changes in g-glutamyl-transferase levels (71 U/L twenty-four hours after ingestion) [146]. A case series showed that vortioxetine (10-20 mg/day) was safe and effective in a sample of nine patients suffering from epilepsy (seven cases were structural, and two were cryptogenetic) without any apparent destabilization of epileptic thresholds [147]. A report found a favourable outcome after three months 10 mg/day vortioxetine treatment in a patient with rapid eye movement (REM) sleep behaviour disorder previously treated with paroxetine and melatonin without benefit [148].…”
Section: Descriptive Observational Studiesmentioning
confidence: 99%
“…U wszystkich pacjentów uzyskano remisję objawów depresji, a leczenie było dobrze tolerowane. U 2 pacjentów zaobserwowano napady drgawkowe, jednak oceniono, że ich wystąpienie nie było związane ze stosowaniem LPD, lecz z nieoptymalnym leczeniem przeciwdrgawkowym [46].…”
Section: Działania Niepożądane I Bezpieczeństwo Wortioksetynyunclassified